Forestry in the Midst of Global Changes - Farcy, Christine; Rojas-Briales, Eduardo; Martinez de Arano, Inazio; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Forestry today, like many other sectors that traditionally rely on material goods, faces significant global drivers of societal change that are less often addressed than the environmental concerns commonly in the spotlight of scientific, political, and news media. There are three major interconnected issues that are challenging forestry at its foundation: urbanization, tertiarization, and globalization. These issues are at the core of this book. The urbanization of society, a process in development from the first steps of industrialization, is particularly significant today with the predominance and quick growth rate of the world$1 (Bs urban population. Ongoing urbanization is creating new perspectives on forestry, inducing changes in its social representation, and changing lifestyles and practices with a tendency toward dematerialization. The process of urbanization is also creating a disconnect and in some ways is leaving behind rurality, the sector of society where forestry has traditionally developed and taken place over centuries. The second issue covered in this book is the tertiarization of the economy. In society today, the sector of services largely dominates the economy and occupies the major part of the world$1 (Bs active population. This ongoing process modifies professional modalities and ways of life and opens new doors to forests through the immaterial goods they provide. It also profoundly changes the framework, rules, processes, means of production, exchanges between economic factors, and the processes of innovation. The third issue is undoubtedly globalization in its economic, political, and social components. Whether it$1 (Bs through bridging distances, crossing borders, accelerating changes, standardizing practices, leveling hierarchical structures, or pushing for interdependence, globalization impacts everyone, everywhere in multiple ways. Forestry is no exception. Forestry in the Midst of Global Changes focuses on these global drivers of change from the perspective of their relationships with how society functions. By analyzing them in depth through multidisciplinary, interdisciplinary, and even transdisciplinary approaches, this book is helping to design the forestry of tomorrow.s
Section I. SETTING THE SCENE -- Introduction -- By the Editorial team -- What is a Forest? -- Paul ARNOULD -- Main Milestones in Forestry Evolution -- Christine FARCY, Inazio MARTINEZ de ARANO and Eduardo ROJAS-BRIALES -- Main Current Ethical Models on the Scene -- Nicole HUYBENS -- Section II. URBANIZATION OF THE SOCIETY -- Main Findings and Trends of Urbanization -- Tahia DEVISSCHER, Lorien NESBITT and Adrina BARDEKJIAN -- Urban lifestyles: Forest Needs and Fears -- Cecil KONIJNENDIJK van den BOSCH -- Toward a Social Representation of Forest by Western Urbanized Societies -- Christine FARCY, Sylvie NAIL, Julie MATAGNE, Anne-Marie GRANET, Olivier BAUDRY and Ewald RAMETSTEINER -- Human Desertification and Disempowerment of Rural Territories -- Eduardo ROJAS-BRIALES, Rafael DELGADO-ARTES and Miguel CABRERA-BONET -- Dendroculture: Social Imaginations, Art and Culture in Forests -- Marti BOADA, Roser MANEJA and Maribel LOZANO -- Communicating to Support the Comprehension of Forest-Related Issues by Non-Expert Audiences -- Julie MATAGNE and Pierre FASTREZ -- Section III. TERTIARIZATION OF THE ECONOMY -- Main Findings and Trends of Tertiarization -- Maria JOSE MURCIA, Meike SIEGNER and Jennifer DEBOER -- Increasing Role of Services: Trends, Drivers and Search for New Perspectives -- Pavi PELLI, Annuka NYH and Lauri HETEMAKI -- Human Health, a Tertiary Product of Forests -- Naomie HERPIN-SAUNIER, Ingrid JARVIS and Matilda van den BOSCH -- Framing Investments in Forest Services -- Patrice HAROU -- Motivation of Service Producers -- Philippe POLOME -- Section IV. GLOBALIZATION -- Main Findings and Trends of Globalization -- Yemi ADEYEYE, Sarah SRA, Jiadong YE and Louise ADAM -- Financialization and the Forestry Sector -- Patrick MEYFROIDT -- Social and Technological Innovations in Forestry -- Laura SECCO, Elena PISANI, Mauro MASIERO and Davide PETTENELLA -- Globalization and Employment in Forests and Tree Product Value Chains: Are Women Losing Out? -- Jennie DEY de PRYCK, Marlne ELIAS, Bimbika SIJAPATI BASNETT -- Fragmented Forest Policy: Asset or Concern? -- Pauline PIRLOT -- Section V. LESSONS LEARNED -- Conclusion and Perspectives -- By the Editorial team.
Also available in print format.
Keywords: bioeconomy; forest policy; governance; social imaginarium; tertiarization; urbanization; Forests and forestry -- Social aspects; Forests and forestry -- Political aspects; Forest management -- Social aspects; TECHNOLOGY & ENGINEERING / Agriculture / Forestry; NATURE / Environmental Conservation & Protection; GARDENING / Fruit; Electronic books